Skrining Prediabetes Dengan Skoring American Diabetes Association (ADA) Pada Calon Jamaah Haji 2025 - Jeem, Yaltafit Abror; Andriani, Russy Novita; Yuantari, Rahma; Asmara, Satria Akbar Putra (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Objective: This study aimed to evaluate the diagnostic validity of the American Diabetes Association (ADA) risk score for prediabetes screening among prospective Hajj pilgrims in 2025.Methods: A diagnostic cross-sectional study was conducted on 232 prospective pilgrims from KBIHU Multazam Addakwah using total sampling. The primary variables were the ADA risk score (cut-off ≥4) and fasting plasma glucose as the reference standard. Data were collected through the ADA risk questionnaire and fasting glucose measurement, then analyzed using ROC curve and diagnostic performance metrics.Results: The prevalence of prediabetes was 10.99%. The ADA risk score demonstrated a sensitivity of 65%, specificity of 57.4%, positive predictive value of 15.8%, negative predictive value of 93%, and overall accuracy of 58.2%. The area under the curve (AUC) was 61.0% (95% CI: 50.7%–71.3%; p=0.042).Conclusion: The ADA risk score shows good exclusion capability for prediabetes but limited discriminatory accuracy, and therefore cannot yet be recommended as a standalone primary screening tool for Indonesian Hajj pilgrims without further modification. Keywords: